2021
DOI: 10.30867/action.v6i2.531
|View full text |Cite
|
Sign up to set email alerts
|

Perbedaan nilai gizi susu sapi setelah pasteurisasi non termal dengan HPEF (High Pulsed Electric Field)

Abstract: Cow's milk is the secretion of a cow that has perfect nutritional value but is easily damaged. Efforts to extend the shelf life of milk, milk is usually stored in a box freezer or by thermal pasteurization. However, this thermal processing can change the smell, taste, colour and reduce the nutritional content of milk, especially protein, which is a heat resistant substance. Alternative non-thermal technology that HPEF can apply. The method of this research was descriptive, describing the nutritional value of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
4
0
3
Order By: Relevance
“…The test results show a rise time value of 0.39 minutes, an overshoot percentage of 0.61%, a minimum settling time of 60.88, and a maximum settling time of 62.38; (4) In testing the activation of the stove using an electric lighter and flame sensor, the threshold value imposed in the range of 1000 to 4000 for the analog output is used to detect the flame at a fixed distance of 10 CM. The purpose of this test is to ensure that the stove ignites successfully at a percentage of 100% when the flame sensor detects the flame; (5) In testing the electric lighter and flame sensor, it can be concluded that the time required to light the stove when the electric lighter is on is 2 seconds, and when the stove is lit, the electric lighter will turn off within 1 second.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The test results show a rise time value of 0.39 minutes, an overshoot percentage of 0.61%, a minimum settling time of 60.88, and a maximum settling time of 62.38; (4) In testing the activation of the stove using an electric lighter and flame sensor, the threshold value imposed in the range of 1000 to 4000 for the analog output is used to detect the flame at a fixed distance of 10 CM. The purpose of this test is to ensure that the stove ignites successfully at a percentage of 100% when the flame sensor detects the flame; (5) In testing the electric lighter and flame sensor, it can be concluded that the time required to light the stove when the electric lighter is on is 2 seconds, and when the stove is lit, the electric lighter will turn off within 1 second.…”
Section: Discussionmentioning
confidence: 99%
“…Bone tissue is formed during puberty, so milk is very suitable for consumption during puberty [4]. The milk's nutrients include protein, calcium, vitamin A, vitamin B, vitamin D, amino acids, calories, fat, phosphorus, iodine, zinc, iron, copper, magnesium, vitamin E, and thiamine [5]. Milk contains high nutrition, which contains water (87.5%), carbohydrates (4.5%), fat (3.6%), protein (3.4%), and minerals (0.75%).…”
Section: Introductionmentioning
confidence: 99%
“…Minyak yang dipakai berulang kali akan menjadi tengik serta dapat merusak asam lemak essential dan terbentuknya produk polimerasi yang beracun. (Budi Hariono, Feby Erawantini, Azamataufiq Budiprasojo, 2021)…”
Section: Pembahasanunclassified
“…Salah satu sumber karbohidrat adalah susu. Susu merupakan produk yang dihasilkan asal ternak yang memiliki fungsi sebagai sumber energi untuk metabolisme tubuh karena memiliki gizi lengkap seperti karbohidrat, protein, lemak, vitamin, dan mineral [1] Selain memiliki nilai gizi yang tinggi, susu sangat bermanfaat untuk kesehatan yaitu: mencegah penyakit jantung dangangguan pembuluh darah, penyakit gondok, meringankan kerja cerebrum, baik untuk penderita anemia, menjaga kesehatan kulit, menjadikan rileks dan tenang [2] membantu pertumbungan gigi dan tulang, memelihara kesehatan, mempercepat penyembuhan, menajamkan penglihatan, sebagai penetralisir zat, mencegah osteoporosis [3] sebagai energi cadangan, mengurangi risiko diabetes tipe 2,menghambat pertumbuhan kanker usus besar, serta menurunkan risiko kanker payudara pada wanita [4].…”
Section: Pendahuluanunclassified